Análisis para implementación de un Sistema de Facturación para la Ferretería Hermanos Chimbo perteneciente al cantón Puebloviejo - Contreras Sánchez, Valeria Véronica (2021)
At present, the use of technology has become a fundamental tool for business competitiveness, where the automation of processes allows to provide the necessary speed in the development of administrative, accounting and commercial activities. The main problem that the Hermanos Chimbo Hardware Store has is the absence of a billing system to help automate business activities; In other words, the organization performs procedures manually, which causes information management to be inefficient and timely; This is why it is necessary to implement an information management system that fosters a better value chain for your commercial transactions. The objective of the research is to analyze the feasibility for the implementation of a billing system in the company under study. The case study methodology has a qualitative approach, with the application of the deductive method to analyze the main research findings; while the type of research used is descriptive, which made it possible to determine the main advantages of the implementation of a web system for invoicing. The interview technique was also applied, directed to the owner manager, which helped to know how the billing process is carried out. In addition, the DoRCU requirements engineering methodology was also applied, since it is necessary for the development of the system. However, evaluative processes of economic, operational and technical feasibility were also applied for the development and implementation of the software.